TEORI HUMANISTIK DALAM MULTIMEDIA PEMBELAJARAN BILANGAN BULAT - Mita Hapsari Jannah; Suyoto Suyoto (Universitas Muhammadiyah Semarang, 2018)
This study aims to develop elementary V class multimedia based on humanistic theory on integer competencies that is valid, practical, and effective. The development model is a 4D (define, design, development, disseminate) model. In the define stage there are interviews and observations to study the curriculum and the needs of teachers and students. In the design stage, draft I multimedia was designed using Adobe Flash Player. In the development stage, draft I is valid based on questionnaires from media and material expert validators. Furthermore, the results of field notes and student and teacher response questionnaires indicate that draft II is practical. Then drat III was tested by independent t-test which resulted that draft III is effective. Draft III developed into a final product which was then disseminated at the disseminate stage with the delivery of products to teachers, training of teachers, and publications in national journals.